The Effect of Resistance Band Training and Full Over Training on Badminton Smash Ability of PB. Fila Watch Makassar - Aswad, Muhammad; Sudiadharma, Sudiadharma; As, Hasbunallah; Hudain, Muh. Adnan; Mappaompo, M. Adam (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of Resistance Band Training on the Smash Shot Ability of Badminton PB. Fila Watch Makassar. The research method is experimental research. In this design, there are two groups selected randomly, then given a pretest to determine the initial condition of whether there is a difference between the Resistance band training group and the full-over training group. The sample taken for this study was 20 Badminton players PB. Fila Watch Makassar City. Based on the results of data analysis, the results of hypothesis testing, and the results of the discussion of the research that have been obtained, the conclusions in this study can be explained. The first is that there is an effect of Resistance Band Training on the Smash Shot Ability of Badminton PB. Fila Watch Makassar is proven by an increase in the average value of 20.40 to 23.80 with a Thit value of 9.619> Ttab 2.262. Second, there is an effect of Full Over Training on the Smash Shot Ability of Badminton PB. Fila Watch Makassar is proven by an increase in the average value of 20.20 to 22.00 with a Thit value of 4.743> Ttab 2.262. The third is a difference in the Effect of Resistance Band Training and Full Over Training on the Ability of Badminton Smash Strokes PB. Fila Watch Makassar with an average value of Resistance Band training 23.80> average value of Full Overtraining 22.00 with a Thit value of 3.818> Ttab 2.101. The conclusion is that Resistance Band training has a greater influence than Full Over Training in improving the ability of Full Over training on Badminton Smash Strokes PB. Fila Watch Makassar.